Emergent publics of alcohol and other drug policymaking - Fraser, Suzanne; Valentine, K.; Seear, K. (2016)
Alcohol and other drug (AOD) policy is developed within complex networks of social, economic, and political forces. One of the key ideas informing this development is that of the ‘public’ of AOD problems and policy solutions. To date, however, little scholarly attention has been paid to notions of the public in AOD policymaking. Precisely how are publics articulated by those tasked with policy development and implementation? In this article, we explore this question in detail. We analyze 60 qualitative interviews with Australian and Canadian AOD policymakers and service providers, arguing that publics figure in these interviews as pre-existing groups that must be managed – contained or educated – to allow policy to proceed. Drawing on Michael Warner’s work, we argue that publics should be understood instead as made in policy processes rather than as preceding them, and we conclude by reframing publics as emergent collectivities of interest. In closing, we briefly scrutinize the widely accepted model of good policy development, that of ‘consultation,’ arguing that, if publics are to be understood as emergent, and therefore policy’s opportunities as more open than is often suggested, a different figure – here that of ‘conference’ is tentatively suggested – may be required.